(untitled) (Journal of Oriental Studies, 2019)
This article analyzes the nature, characteristics and prospects of the development of socialism with Chinese characteristics. The theoretical and practical essence of the development of socialism in China and the true nature of modern Chinese socialism for the realization of national revival and the creation of a just and universal rich society are also determined. Key words: Datong, Chinese socialism, modernization, xiaokang, middle-income society (xiaokangshehui), society of universal prosperity (Fuyishehui), Asian values.